1983
DOI: 10.2527/jas1983.563570x
|View full text |Cite
|
Sign up to set email alerts
|

Index Selection and Feed Intake Restriction in Swine. II. Effect on Energy Utilization

Abstract: SummaryFifty-three index select and control line barrows were randomly assigned to three feeding levels at 83 d of age. They were slaughtered at approximately 188 d of age to determine the effects of index selection (for increased average daily gain and decreased backfat) and level of feed intake on energy utilization. During the trial, the feed intake levels were twice daily to appetite (AP), once daily feeding of 91% of appetite (AP91) or once daily feeding of 82% of appetite (AP82) intake. The metabolizable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
4
2
1
Order By: Relevance
“…This indicates that the Select line is partitioning less of the consumed energy for maintenance requirements than the Control line. These results, however, disagree with the findings from (Cleveland et al, 1983), who found that leaner pigs partition more of their metabolizable energy for maintenance relative to fat pigs. In the current study, the Select line was leaner than the…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that the Select line is partitioning less of the consumed energy for maintenance requirements than the Control line. These results, however, disagree with the findings from (Cleveland et al, 1983), who found that leaner pigs partition more of their metabolizable energy for maintenance relative to fat pigs. In the current study, the Select line was leaner than the…”
Section: Discussioncontrasting
confidence: 99%
“…It has been estimated that maintenance functions account for 70 to 75% of total energy expenditure in the producing female and anywhere from 35 to 50% in growing and fi nishing animals (Ferrell, 1988). Studies have indicated that variation in ME M requirements can be partially explained by the variation in body composition (i.e., lean and fat tissue) and associated metabolic processes (Ferrell et al, 1979;Cleveland et al, 1983). Other contributors to the ME M requirement of an animal are body tissues (i.e., visceral organs) with high metabolic activity, particularly the liver and digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Sather and Fredeen (1978), Vangen (1979 and1980) and Cleveland et al (1982), Cleveland, Johnson, Mandigo and Peo (1983) selected on lean growth indices, essentially equal to growth rate minus backfat depth, expressed in phenotypic standard deviation units, and reported increased growth rate with reductions in backfat and FCR. Sather and Fredeen (1978), Vangen (1979 and1980) and Cleveland et al (1982), Cleveland, Johnson, Mandigo and Peo (1983) selected on lean growth indices, essentially equal to growth rate minus backfat depth, expressed in phenotypic standard deviation units, and reported increased growth rate with reductions in backfat and FCR.…”
Section: Discussionmentioning
confidence: 99%